Perioperative blood transfusion is not associated with overall survival or time to recurrence after resection of perihilar cholangiocarcinoma. Issue 3 (March 2016) - Dekker, Annemiek M.; Wiggers, Jimme K.; Coelen, Robert J.; van Golen, Rowan F.; Besselink, Marc G.H.; Busch, Olivier R.C.; Verheij, Joanne; Hollmann, Markus W.; van Gulik, Thomas M.
Abstract: Background: Perioperative blood transfusions have been associated with worse oncological outcome in several types of cancer. The objective of this study was to assess the effect of perioperative blood transfusions on time to recurrence and overall survival (OS) in patients who underwent curative-intent resection of perihilar cholangiocarcinoma (PHC). Methods: This retrospective cohort study included consecutive patients with resected PHC between 1992 and 2013 in a specialized center. Patients with 90-day mortality after surgery were excluded. Patients who did and did not receive perioperative blood transfusions were compared using univariable Kaplan–Meier analysis and multivariable Cox regression. Results: Of 145 included patients, 80 (55.2%) received perioperative blood transfusions. The median OS was 49 months for patients without and 41 months for patients with blood transfusions (P = 0.46). In risk-adjusted multivariable Cox regression analysis, blood transfusion was not associated with OS (HR 1.00, 95% CI 0.59–1.68, P = 0.99) or time to recurrence (HR 1.00, 95% CI 0.57–1.78, P = 0.99). In addition, no differences in effect were found between different types of blood products transfused. Conclusion: Blood transfusion was not associated with survival or time to recurrence after curative resection of PHC in this series. The alleged association is presumably related to the circumstances necessitating blood transfusions.